(3GdLGeY GdcGajs - (3YR GdOjf eMeO Hf Ydj GdMSfjs ((3GdMSf Hf eMeO Hf jMji GdCNaT s)
(3ChdgG (B:s
(3CeG HYO aEfc PcQJ di Cfc QGjJ GdRjOjI bHdfG HGdchaI jbhdhf ai eSGFd GdNdGa Ydi ePPgH C;eO Hf YjSi hPcQJ Cf CbGhjdge eJaQbI djS jLeYgG cJGH hSCdJ Cf GNJUQ dc efgG cJGHkG GLeY ajg s
(3BNQgG (B:s
(3jfJgi CKfGA eSFdI ai GdChbGa hGdCSfGb s
(3GdfSNI HgG MhGTs
(3LeYg eDdag ef eGFg hKdGKjf eUfakG ef eUfaGJ eMeO Hf efUhQ Hf SYjO GdeQGOi Gdchais
(3fSNI eUMMI s
(3Ydi WQJgG JedcGJ hhbajGJ s
(3cJHJ GdahGJM HGdSejc s
(3bQf GdfSN (B:s
Keywords: (3Gdabg GdESdGejs